Untangling the Contribution of the Subcomponents of Working Memory to Mathematical Proficiency as Measured by the National Tests: A Study among Swedish Third Graders - Wiklund-Hörnqvist, Carola; Jonsson, Bert; Korhonen, Johan; Eklöf, Hanna; Nyroos, Mikaela (Frontiers in Psychology, 2016)
The aim with the present study was to examine the relationship between the subcomponents in working memory and mathematical performance, as measured by the National tests, in a sample of 597 Swedish third-grade pupils. In line with compelling evidence of other studies, individual differences in working memory capacity significantly predicted mathematical performance. Dividing the sample into four groups, based on their mathematical performance, revealed that mathematical ability can be conceptualized in terms of different working memory profiles. Pupils categorized as High-math performers particularly differed from the other three groups in having a significant higher phonological ability. In contrast, pupils categorized as Low-math performers were particularly characterized by having a significant lower visuo-spatial ability. Findings suggest that it is important for educators to recognize and acknowledge individual differences in working memory to support mathematical achievement at an individual level.